Efficacy and safety of zonisamide in thai children and adolescents with intractable seizures - Lunliya Thampratankul (2018)
© The Author(s) 2014. This retrospective study examined the efficacy and safety of zonisamide for Thai children and adolescents with intractable seizures. The medical records of 24 patients (13 male, 11 female), aged 2 to 18 years (median 11.5, mean 10.4) who received zonisamide were reviewed. The underlying illness, etiology of epilepsy, seizure types, previous and concomitant antiepileptic drugs, dosage, and adverse effects of the drug were collected. Zonisamide's efficacy was evaluated on the basis of seizure reduction rates. At final evaluation, 7 patients were still taking zonisamide from 4.7 to 10.3 mg/kg/d (median 8). One patient became seizure-free and the other 6 experienced favorable seizure control. The median duration of zonisamide therapy was 23.75 months (range 20.5-25 months). Minor adverse effects were reported in 41.6% of patients during the first 3 months of therapy. Zonisamide is an option for the treatment of intractable seizures with favorable seizure control in children and adolescents.